Optimization of spectrally selective 180° radiofrequency pulse timings in J‐difference editing (MEGA) of lactate. Issue 3 (17th October 2021) - Ganji, Sandeep K.; An, Zhongxu; Tiwari, Vivek; Chang, Yongmin; Patel, Toral R.; Maher, Elizabeth A.; Choi, Changho
Abstract : Purpose: J‐Difference editing (MEGA) provides an effective spectroscopic means of selectively measuring low‐concentration metabolites having weakly coupled spins. The fractional inphase and antiphase coherences are determined by the radiofrequency (RF) pulses and inter‐RF pulse intervals of the sequence. We examined the timings of the spectrally selective editing 180° pulses (E180) in MEGA‐PRESS to maximize the edited signal amplitude in lactate at 3T. Methods: The time evolution of the lactate spin coherences was analytically and numerically calculated for non‐volume localized and single‐voxel localized MEGA sequences. Single‐voxel localized MEGA‐PRESS simulations and phantom experiments were conducted for echo time (TE) 60–160 ms and for all possible integer‐millisecond timings of the E180 pulses. Optimized E180 timings of 144, 103, and 109 ms TEs, tailored with simulation and phantom data, were tested in brain tumor patients in vivo. Lactate signals, broadened to singlet linewidths (~6 Hz), were compared between simulation, phantom, and in vivo data. Results: Theoretical and experimental data indicated consistently that the MEGA‐edited signal amplitude and width are sensitive to the E180 timings. In volume‐localized MEGA, the lactate peak amplitudes in E180‐on and difference spectra were maximized at specific E180 timings for individual TEs, largely due to the chemical‐shift displacement effects. The E180 timings for maximum lactate peak amplitude were different from those of maximum inphase coherence in in vivo linewidth situations. Conclusion: In in vivo MEGA editing, the E180 pulse timings can be effectively used for manipulating the inphase and antiphase coherences and increasing the edited signal amplitude, following TE optimization.